Establishing a trauma center in Nicosia, Cyprus: lessons from the frontline of system reform - Bartsokas, Christos; Georgiou, Chrysanthos (International Surgery Journal, 2025)
The establishment of a dedicated trauma center at Nicosia General Hospital marks a milestone in Cyprus’s acute care and emergency medicine. Historically, trauma care in Cyprus was fragmented, with cases managed across general hospitals lacking centralized triage, integrated prehospital coordination, and specialized teams. This editorial reflects on the challenges and strategies involved in creating a functional trauma hub in a resource-limited environment. Key barriers included institutional inertia, infrastructure constraints, and the absence of standardized trauma training pathways. Solutions involved repurposing existing resources, implementing evidence-based protocols, introducing tiered trauma activation systems, and fostering interdepartmental collaboration. Prehospital integration was achieved through real-time communication with EMS and formalized transfer agreements, despite resistance from peripheral facilities. Workforce readiness was addressed via targeted, rapid training initiatives drawing on local and international expertise. Cultural change proved as critical as technical capacity, requiring sustained engagement, daily debriefings, performance audits, and leadership support to embed a protocol-driven, multidisciplinary approach. The Cyprus experience demonstrates that with strategic planning, adaptive leadership, and collaboration, effective trauma systems can emerge even under budgetary and logistical constraints. These lessons may guide other regions seeking to establish or reform trauma care infrastructure in similar settings.